An evaluation of the supply risk for China's strategic metallic mineral resources. (March 2021) - Yu, Shiwei; Duan, Haoran; Cheng, Jinhua
Abstract: An important issue for ensuring a nation's economic security involves evaluating the supply risk of its strategic mineral resources. Considering the impact of strategic emerging industries on the supply risk of China's strategic minerals, this study establishes an indicator system for evaluating such risks. Specifically, using stochastic multi-criteria acceptability analysis for the ELimination Et Choix Traduisant la REalité TRI method, this study systematically evaluates the supply risk of 14 strategic metallic mineral resources in China from 2008 to 2017 and through 2025. The results indicate that: 1) From 2008 to 2017, the supply risk level of molybdenum and rare earth elements were low or low-to-medium, and those of 12 other minerals were high or medium-to-high; 2) For copper, gold, tungsten, molybdenum, antimony, and lithium, the supply risk level increased, and that for nickel decreased, while for iron, tin, chromium, and rare earth elements it irregularly fluctuated; and 3) The supply risk of chromium, molybdenum, lithium, and rare earth elements was influenced by potentially higher risk factors caused by poor substitutability and low recycling rate. Highlights: Evaluating indicators of strategic metallic minerals' supply risk is proposed. SMAA-TRI method is used to evaluate risk of fourteen minerals. Supply risks of 12 metallic minerals are at high and medium-high levels. Supply risk of nine minerals is expected to increase from 2018 to 2025.